2018
DOI: 10.1111/jvp.12485
|View full text |Cite
|
Sign up to set email alerts
|

The bioequivalence of a single intravenous administration of the anesthetic alfaxalone in cyclodextrin versus alfaxalone in cyclodextrin plus preservatives in cats

Abstract: To demonstrate the bioequivalence of alfaxalone in cyclodextrin (Reference Product) to a formulation of alfaxalone in cyclodextrin also containing the preservatives ethanol, chlorocresol, and benzethonium chloride (Test Product) when administered for the purpose of inducing anesthesia in the cat. Blinded, single-dose, randomized, two-period, twosequence, cross-over bioequivalence study with a 7-day washout period between treatments. Twenty-four (12 neutered males and 12 intact females), healthy, adult cats wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…In this study, blood pharmacokinetic parameters were calculated using the non-compartmental analysis model 200 (intravenous or extravascular dosing, linear/log trapezoidal method) in the WinNonlin™ software (version 8.1; Certara USA) and WinNonlin 8.1 was used for bioequivalence analysis. Analysis of variance (ANOVA) was used to calculate a 90% CI for the ratio of the two treatments ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, blood pharmacokinetic parameters were calculated using the non-compartmental analysis model 200 (intravenous or extravascular dosing, linear/log trapezoidal method) in the WinNonlin™ software (version 8.1; Certara USA) and WinNonlin 8.1 was used for bioequivalence analysis. Analysis of variance (ANOVA) was used to calculate a 90% CI for the ratio of the two treatments ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The anesthetic properties of alfaxalone have been known since 1971, but due to adverse reactions it was withdrawn from the market, after which it returned in 2001 in a new formulation. In the new presentation, it was complexed with HP-β-CD aiming to increase solubility and bioavailability [ 85 , 86 , 87 , 88 ].…”
Section: Other Inclusion Complexes Used In Veterinary Therapymentioning
confidence: 99%
“…Alfaxalone is a synthetic neuroactive steroid which interacts with the yaminobutyric acid (GABA) receptors of the central nervous system, producing anesthesia and muscle relaxation [6]. When comparing their effects, propofol is associated with decreases in heart rate and mean arterial pressure, and also promote respiratory depression [7]; alfaxalone does not accumulate in tissues after repeated doses due to its rapid metabolism and clearance [7], and also has been reported that cardiovascular and respiratory parameters remained remarkably stable during general anesthesia [8].…”
Section: Introductionmentioning
confidence: 99%